2006
DOI: 10.1182/blood-2006-04-016113
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism for BCR-ABL action: stimulated secretion of CCN3 is involved in growth and differentiation regulation

Abstract: IntroductionChronic myeloid leukemia (CML) is a clonal disorder of pluripotent hematopoietic cells that is characterized by the presence of the Philadelphia chromosome (Ph ϩ ), the result of a reciprocal translocation between chromosomes 9 and 22. The translocation encodes a chimeric protein, BCR-ABL, which is a constitutively activated protein tyrosine kinase (PTK) 1 and which has an essential role in the molecular pathology of CML. CML is a progressive disease with an initial chronic phase in which there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 50 publications
4
64
0
1
Order By: Relevance
“…Again, and from another type of cancer perspective, studies from the Irvine lab (McCallum et al 2006(McCallum et al , 2009Suresh et al 2013) investigating the role of CCN3 in myelopoiesis and leukemia, provided evidence that exogenous CCN3 decreases NOTCH1 signaling and BCR-ABL causes downregulation of CCN3 allowing the NOTCH1 drive to continue suggesting a form of combinatorial therapy including CCN3. Whether future studies will identify similar therapeutic permutations involving CCN proteins have yet to be realized.…”
Section: Ccn3 (Nov)mentioning
confidence: 99%
“…Again, and from another type of cancer perspective, studies from the Irvine lab (McCallum et al 2006(McCallum et al , 2009Suresh et al 2013) investigating the role of CCN3 in myelopoiesis and leukemia, provided evidence that exogenous CCN3 decreases NOTCH1 signaling and BCR-ABL causes downregulation of CCN3 allowing the NOTCH1 drive to continue suggesting a form of combinatorial therapy including CCN3. Whether future studies will identify similar therapeutic permutations involving CCN proteins have yet to be realized.…”
Section: Ccn3 (Nov)mentioning
confidence: 99%
“…Primer and probe sets for CCN3, Integrins alpha 6, beta 1 and beta 4 were designed against Genbank published sequences in association with Primer Express (Applied Biosystems). CCN3 primers and probe set were used as previously described (McCallum et al 2006) having the 5′ reporter 6-carboxyfluorescein (FAM) and the 3′ quencher 6-carboxy-tetramethylrhodamine (TAMRA). The amplification reactions (12.5 μL) contained 50 ng cDNA equivalents (or control), 1×Taqman universal PCR master mix, final concentrations of 5 mM MgCl 2, 0.2 mM deoxyadenosine deoxycytosine deoxyguanosine triphosphate (dATP/ dCTP/ dGTP), 0.4 mM deoxyuridine triphosphate (dUTP), 0.125 U AmpliTaq Gold, 2 μM primers (forward and reverse) and 200 nM TaqMan probe.…”
Section: Rq-pcrmentioning
confidence: 99%
“…Our group were the first to identify a role for CCN3 in haematological malignancy showing CCN3 was downregulated as a result of the BCR-ABL oncogene in CML (McCallum et al 2006). CML is a clonal disorder of pluripotent haematopoietic stem cells and CML progenitor cells possess a subtle defect in cell maturation (Wong and Witte 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone marrow cells from CML patients had reduced Ccn3 expression and the expression was restored upon treatment with imatinib. Increased secretion of Ccn3 is also observed in progenitor CD34 + CML cells, indicating loss of CCN3 as an early event in CML (McCallum et al 2006). In vitro studies using CML cell lines overexpressing Ccn3 or treated with recombinant Ccn3 showed reduced cell proliferation and increased apoptosis (McCallum et al 2009).…”
Section: Introductionmentioning
confidence: 99%